Chronological changes in epidemiological characteristics of lower urinary tract urolithiasis in Japan. (11th October 2018) - Sakamoto, Shinichi; Miyazawa, Katsuhito; Yasui, Takahiro; Iguchi, Taro; Fujita, Misuzu; Nishimatsu, Hiroaki; Masaki, Takuro; Hasegawa, Toru; Hibi, Hatsuki; Arakawa, Takashi; Ando, Ryosuke; Kato, Yoshinari; et al.
Abstract : Objectives: To determine changes and trends in the annual incidence and epidemiological aspects of lower urinary tract stones in Japan. Methods: Data about patients who had been diagnosed by urologists in 2015 with first and recurrent lower urinary tract stones were collected from 301 hospitals approved by the Japanese Board of Urology. The estimated annual incidence according to sex, age and stone composition was compared with previous nationwide surveys between 1965 and 2005. Results: The incidence of lower urinary tract stones in Japan has steadily increased from 4.7 per 100 000 in 1965 to 12.0 per 100 000 in 2015. However, the age standardized annual incidence of lower urinary tract stones has remained relatively stable over the same period at 5.5 per 100 000 and 6.0 per 100 000 in 1965 and 2015, respectively. The increase in incidence was most evident among individuals aged ≥80 years. The incidence of calcium oxalate stones has steadily increased among males and females, whereas that of infection‐related stones has significantly decreased from 26.2% to 14.3% among men over the past 50 years. Conclusions: Nationwide surveys suggest a steady increase in the incidence of lower urinary tract stones over a 50‐year period in Japan. This trend might reflect changes in the aging population and improved Japanese medical standards.